Diabetic retinopathy is a ceramidopathy reversible by anti-ceramide immunotherapy - Dorweiler, Tim F.; Singh, Arjun; Ganju, Aditya; Lydic, Todd A.; Glazer, Louis C.; Kolesnick, Richard N.; Busik, Julia V. (Cell metabolism, 2024)
Diabetic retinopathy is a microvascular disease that causes blindness. Using acid sphingomyelinase knockout mice, we reported that ceramide generation is critical for diabetic retinopathy development. Here, in patients with proliferative diabetic retinopathy, we identify vitreous ceramide imbalance with pathologic long-chain C16-ceramides increasing and protective very long-chain C26-ceramides decreasing. C16-ceramides generate pro-inflammatory/pro-apoptotic ceramide-rich platforms on endothelial surfaces. To geo-localize ceramide-rich platforms, we invented a three-dimensional confocal assay and showed that retinopathy-producing cytokines TNFα and IL-1β induce ceramide-rich platform formation on retinal endothelial cells within seconds, with volumes increasing 2-logs, yielding apoptotic death. Anti-ceramide antibodies abolish these events. Furthermore, intravitreal and systemic anti-ceramide antibodies protect from diabetic retinopathy in standardized rodent ischemia reperfusion and streptozotocin models. These data support (1) retinal endothelial ceramide as a diabetic retinopathy treatment target, (2) early-stage therapy of non-proliferative diabetic retinopathy to prevent progression, and (3) systemic diabetic retinopathy treatment; and they characterize diabetic retinopathy as a “ceramidopathy” reversible by anti-ceramide immunotherapy. [Display omitted] •Vitreous C16:0/26:0 ceramide ratio is increased in proliferative diabetic retinopathy•C16-ceramide forms pro-inflammatory and pro-apoptotic ceramide-rich platforms•Cytokines induce ceramide-rich platform formation on retinal endothelial cells•Retinal microvascular injury in diabetes is reversed by anti-ceramide immunotherapy Diabetic metabolic abnormalities cause retinal “ceramidopathy,” with sphingolipid imbalance leading to pathological ceramide-rich platform formation on the surface of retinal endothelial cells. Anti-ceramide antibodies targeting ceramide-rich platforms inhibit diabetes-induced endothelial cell apoptosis, dysfunction, and increased permeability. Intravitreal and systemic anti-ceramide immunotherapy reverse retinal microvascular injury in diabetic retinopathy.